PELATIHAN FITUR OTOMATISASI DOKUMEN MICROSOFT WORD UNTUK MENINGKATKAN KETERAMPILAN PENYUSUNAN DOKUMEN AKADEMIK DI STMIK LOMBOK - Zulkipli; Amir Bagja; Zaenul Amri; M Nurul Wathani; Muhamad Rodi (Jurnal Pekayunan, 2025)
This training activity aims to enhance participants' skills in utilizing Microsoft Word’s document automation features, including automatic table of contents creation, figure listing, page numbering, and cross-referencing. The training was conducted in the REC Room of STMIK Lombok on Wednesday, May 28, 2025, involving 40 participants. The method used was a hands-on approach (learning by doing), and participants were evaluated through pre-test and post-test assessments. The pre-test results showed that 17 participants were in the "not capable" category, and none were categorized as "highly capable". After the training, the post-test revealed significant improvement, with 33 participants achieving the "highly capable" category. This activity has proven effective in equipping participants with essential document processing skills needed in academic settings. It is recommended that similar training be held regularly within campus environments or other institutions aiming to strengthen digital academic literacy.